Cross‐Isotopic Bioorthogonal Tools as Molecular Twins for Radiotheranostic Applications. (8th May 2019) - Rosecker, Veronika; Denk, Christoph; Maurer, Melanie; Wilkovitsch, Martin; Mairinger, Severin; Wanek, Thomas; Mikula, Hannes
Abstract: Radiotheranostics are designed by labeling targeting (bio)molecules with radionuclides for diagnostic or therapeutic application. Because the pharmacokinetics of therapeutic compounds play a pivotal role, chemically closely related imaging agents are used to evaluate the overall feasibility of the therapeutic approach. "Theranostic relatives" that utilize different elements are frequently used in clinical practice. However, variations in pharmacokinetics, biodistribution, and target affinity due to different chemical properties of the radioisotopes remain as hurdles to the design of optimized clinical tools. Herein, the design and synthesis of structurally identical compounds, either for diagnostic ( 18 F and a stable metal isotope) or therapeutic application (radiometal and stable 19 F), are reported. Such "molecular twins" have been prepared by applying a modular strategy based on click chemistry that enables efficient radiolabeling of compounds containing a metal complex and a tetrazine moiety. This additional bioorthogonal functionality can be used for subsequent radiolabeling of (bio)molecules or pretargeting approaches, which is demonstrated in vitro. Abstract : Chemical lookalikes : A modular approach for the synthesis of chemically identical "cross‐isotopic" agents for theranostic applications is reported. These compounds contain a chelator for the introduction of therapeutic radiometals or the respective stable metal isotopes, and can be labeled with 18 F or stable 19 F by click chemistry.